PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN PEMBENTUKAN KARAKTER SISWA KELAS VIII DI SMP PGRI PAGARALAM - Imam Subhi; Yesi Marsela; Rahman Yahan (Jurnal Genta Mulia, 2023)
This research relates to the role of Islamic religious education teachers in promoting the character formation of class VIII students at PGRI Pagar Alam Middle School. The aim of the research is to find out the role of Islamic Religious Education teachers in improving the character formation of class VIII students and to find out what the supporting and inhibiting factors are in improving the character formation of class VIII students at SMP PGRI Pagar Alam. This type of research is descriptive qualitative. Observation, interview and documentation data collection techniques. The results of this research are that the role played by Islamic Religious Education Teachers in Improving the Character Formation of Class VIII Students at PGRI Pagar Alam Middle School has played a good role, where Islamic Religious Education teachers have played their roles as teachers, mentors, leaders, scientists, and as individuals who Good. Meanwhile, the supporting factors in improving student character formation are the very active role of teachers, fellow educators and peers, school programs and inhibiting factors, namely the progress of IFTEK, the number of parents who defend their children even though the child has made a mistake, the surrounding environment. , there is a lack of student awareness of the importance of character building, interacting with peers and also social media.